Cardiovascular disease and renal function - Zh. D. Kobalava; S. V. Villevalde; V. S. Moiseev (Российский кардиологический журнал)
Cardiorenal interactions are one of the important and widely discussed problems of modern medicine. The paper discusses the evolution of the medical views on cardiorenal syndromes and chronic kidney disease. Russian and international data on prevalence, prognostic value, pathophysiologic mechanisms, prevention, and treatment of these conditions are presented. The authors discuss unresolved issues and potential directions of future research in the field of cardiorenal medicine.